Determinants of the risk of dying of HIV/AIDS in a rural South African community over the period of the decentralised roll-out of antiretroviral therapy: a longitudinal study - Paul Mee; Mark A. Collinson; Sangeetha Madhavan; Chodziwadziwa Kabudula; Francesc Xavier Gómez-Olivé; Kathleen Kahn; Stephen M. Tollman; James Hargreaves; Peter Byass (Taylor & Francis Group, 2014)
Background: Antiretroviral treatment (ART) has significantly reduced HIV mortality in South Africa. The benefits have not been experienced by all groups. Here we investigate the factors associated with these inequities. Design: This study was located in a rural South African setting and used data collected from 2007 to 2010, the period when decentralised ART became available. Approximately one-third of the population were of Mozambican origin. There was a pattern of repeated circular migration between urban areas and this community. Survival analysis models were developed to identify demographic, socioeconomic, and spatial risk factors for HIV mortality. Results: Among the study population of 105,149 individuals, there were 2,890 deaths. The HIV/TB mortality rate decreased by 27% between 2007-2008 and 2009-2010. For other causes of death, the reduction was 10%. Bivariate analysis found that the HIV/TB mortality risk was lower for: those living within 5 km of the Bhubezi Community Health Centre; women; young adults; in-migrants with a longer period of residence; permanent residents; and members of households owning motorised transport, holding higher socioeconomic positions, and with higher levels of education. Multivariate modelling showed, in addition, that those with South Africa as their country of origin had an increased risk of HIV/TB mortality compared to those with Mozambican origins. For males, those of South African origin, and recent in-migrants, the risk of death associated with HIV/TB was significantly greater than that due to other causes. Conclusions: In this community, a combination of factors was associated with an increased risk of dying of HIV/TB over the period of the roll-out of ART. There is evidence for the presence of barriers to successful treatment for particular sub-groups in the population, which must be addressed if the recent improvements in population-level mortality are to be maintained.